Ecopipam, a D1 receptor antagonist, for treatment of tourette syndrome in children: A randomized, placebo‐controlled crossover study. Issue 8 (7th September 2018) - Gilbert, Donald L.; Murphy, Tanya K.; Jankovic, Joseph; Budman, Cathy L.; Black, Kevin J.; Kurlan, Roger M.; Coffman, Keith A.; McCracken, James T.; Juncos, Jorge; Grant, Jon E.; Chipkin, Richard E.
Abstract: Background : Dopamine D2 receptor antagonists used to treat Tourette syndrome may have inadequate responses or intolerable side effects. We present results of a 4‐week randomized, double‐blind, placebo‐controlled crossover study evaluating the safety, tolerability, and efficacy of the D1 receptor antagonist ecopipam in children and adolescents with Tourette syndrome. Methods : Forty youth aged 7 to 17 years with Tourette syndrome and a Yale Global Tic Severity Scale – total tic score of ≥20 were enrolled and randomized to either ecopipam (50 mg/day for weight of <34 kg, 100 mg/day for weight of >34 kg) or placebo for 30 days, followed by a 2‐week washout and then crossed to the alternative treatment for 30 days. Stimulants and tic‐suppressing medications were excluded. The primary outcome measure was the total tic score. Secondary outcomes included obsessive compulsive and attention deficit/hyperactivity disorder scales. Results : Relative to changes in placebo, reduction in total tic score was greater for ecopipam at 16 days (mean difference, ‐3.7; 95% CI, ‐6.5 to ‐0.9; P = 0.011) and 30 days (mean difference, ‐3.2; 95% CI, ‐6.1 to ‐0.3; P = 0.033). There were no weight gain, drug‐induced dyskinesias, or changes in laboratory tests, electrocardiograms, vital signs, or comorbid symptoms. Dropout rate was 5% (2 of 40). Adverse events reported for both treatments were rated predominantly mild to moderate, with only 5 rated severe (2 for ecopipam and 3 for placebo). Conclusions : Ecopipam reduced tics and was well tolerated. This placebo‐controlled study of ecopipam supports further clinical trials in children and adolescents with Tourette syndrome. © 2018 International Parkinson and Movement Disorder Society